Mapping Land Vulnerability to Degradation using a Geographic Information System (GIS) - Ruth Riah Ate Tarigan (SEAN Institute, 2026)
Land degradation poses a significant threat to environmental sustainability and agricultural productivity, particularly in regions experiencing rapid land-use change and increasing anthropogenic pressure. Mapping land vulnerability to degradation is essential for supporting effective land management and spatial planning policies. This study aims to assess and map land vulnerability to degradation using a Geographic Information System (GIS) approach. The analysis integrates multiple biophysical and environmental factors, including slope, soil type, land use/land cover, rainfall intensity, and vegetation index. A weighted overlay method was applied, with factor weights determined using expert judgment and relevant literature to generate a land degradation vulnerability index. The results classify the study area into low, moderate, and high vulnerability zones. Areas with steep slopes, sparse vegetation cover, and intensive land use exhibit the highest vulnerability to degradation. The vulnerability map highlights spatial patterns that can support targeted land management interventions and conservation planning. This study demonstrates that GIS-based spatial analysis provides an effective and reliable framework for identifying land degradation risks and offers valuable insights for policymakers in promoting sustainable land management and mitigating land degradation impacts.